Hypopigmented Mycosis Fungoides: A Clinical and Histopathology Analysis in 9 Children. (April 2021) - Chen, Yunliu; Xu, Jiaosheng; Qiu, Lei; Fu, Libing; Liang, Yuan; Wei, Li; Xiang, Xin; Wang, Zhaoyang; Xu, Zigang; Ma, Lin
Abstract : Background: Hypopigmented mycosis fungoides (HMF) is an uncommon variant of mycosis fungoides. Aims: To study the clinical and histopathology presentation in children with HMF. Method: We reviewed 9 children diagnosed with HMF. The clinical data were collected and analyzed. Result: Eight boys and 1 girl were included, with a median onset age of 7.4 year old and median age of diagnosis of 10.5 year old. Multiple hypopigmented patches were observed in all patients, and 5 patients exhibited multiple scaly erythema at the center of hypopigmented patches. Histopathology showed atypical lymphocytes with hyperchromatic, irregular, and cerebriform nuclei, infiltrated in the epidermis and dermis. Pautrier's microabscesses was noted in 6 of 9 patients, and papillary dermal fibroplasia was noted in 6 of 9 patients. CD8 predominance was detected in 4 of 6 patients. Four patients were simultaneously subjected to skin biopsy on hypopigmented patches and scaly erythema simultaneously. Compared with hypopigmented specimens, erythema biopsy detected deeper and denser infiltration of atypical lymphoid cells in 3 of 4 patients, higher CD4 + /CD8 + ratio in 4 of 4 patients, more CD5 loss in 2 of 4 patients, and more CD7 loss in 2 of 4 patients. TCR gene monoclonal rearrangement was detected in 2 of 5 patients. Narrowband ultraviolet B phototherapy was applied in 7 patients. One of 7 patients achieved complete response, and 6 of 7 patients achieved partial response. No recurrence was noted with the median follow-up period of 6 months. Conclusion: HMF could occur in young patients, with indolent and benign course. HMF could gradually seem as scaly erythema based on hypopigmented patches. The histopathology indicated a more advanced stage of the scaly erythema lesions than hypopigmented patches.